EPIDEMIOLOGIA DA SÍFILIS CONGÊNITA NO ESTADO DE GOIÁS - Vitória Castilho Amâncio; Annah Rachel Graciano; Andressa Meline Coze; Luís Pedro Ferreira de Assis; Divanita Cândida da Silva Dias (UniEVANGÉLICA, 2017)
Objective: To describe the occurrence and epidemiological profile of reported congenital syphilis cases in the state of Goiás, 2007-2010. Methods: Descriptive ecological study with temporal trend design. The data used were from the Information on Live Births and the System of Information of Notification Diseases. Results: A total of 538 (100%) cases of congenital syphilis were confirmed, of which 504 (94%) were 6 days old. The year of 2012 presented the highest number of such occurrences, with 113 (21%). Regarding the health area of the Southern Region, the confirmed cases were 280 (52%). In 135 cases (25%), women had up to 8 years of education. 427 (80%) women received prenatal care. In 248 (47%) cases, the diagnosis of maternal syphilis occurred in the prenatal period, which identified the greatest number of recent diagnostic congenital syphilis 481 (89%). The number of cases in which the partner received treatment was 95 cases (18%). The highest incidence rate was in 2012 (1.2/1,000 inhabitants). Conclusion: Despite the decrease in the incidence rate of congenital syphilis in the state of Goiás in the period investigated in 2013, this rate was still higher than the 0.5 per 1,000 live births, a goal established to eliminate the disease.